Experimental analysis of a photovoltaic/thermoelectric generator using cobalt oxide nanofluid and phase change material heat sink. (15th May 2020) - Rajaee, Fatemeh; Rad, Mohammad Amin Vaziri; Kasaeian, Alibakhsh; Mahian, Omid; Yan, Wei-Mon
Highlights: The performance of a photovoltaic-thermoelectric hybrid system is investigated. An integrated phase change material/cobalt oxide nanofluid heat sink is proposed. Around 14% higher electrical power is experimentally achieved by this heat sink. The exergy efficiency of the unit is improved by 17.8% at noon. Abstract: Nowadays, photovoltaic panels have been known as effective devices to harness solar energy. These panels mainly convert the UV and visible areas of the solar spectrum into electricity and the rest of the energy is dissipated. One of the favorable methods to take advantage of such dissipated heat is to combine thermoelectric generators (TEG) utilizing the IR area of the solar radiation with photovoltaic panels. Having the different and opposite impact on the efficiency of thermal photovoltaic cells (PV/T) and thermoelectric generators (TEG), the system operating temperature appears as a critical parameter in the productivity of a PV/T-TEG hybrid unit. In the present study, a novel heat sink for a PV/T-TEG hybrid system is introduced. The effectiveness of simultaneous usage of the Co3 O4 /water nanofluid and the improved phase change material (paraffin wax/Alumina powder) as a cooling method on the performance of the PV/T-TEG is examined throughout an experimental study. Then, the overall electrical, thermal and exergy efficiency of such a system is compared to the units with divers working fluids including water and 0.25%, 0.5%, and 1% nanofluid and the unit consisting of 1% nanofluid with non-enhanced PCM cooling method. The results reveal that using 1% nanofluid with enhanced PCM, as a cooling method, would improve the overall electrical efficiency by 12.28% compared to water cooling technique. Also, an increase of 11.6% in the exergy efficiency of the PV/T-TEG is observed in comparison with PV/T-TEG with the water cooling method. Hence, it could be concluded that the combination of this unit could contribute to harnessing solar energy more efficiently, compared to solo photovoltaic panels.